2008
DOI: 10.1248/bpb.31.497
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Determination of Both Thalidomide Enantiomers Using HPLC Systems

Abstract: Over the last few years, thalidomide has become one of the most important anti-tumour drugs for the treatment of relapsed-refractory multiple myeloma. However, besides its undesirable teratogenic side effect, its configurational instability critically limits any further therapeutic improvements of this drug. In 1999, we developed fluoro-thalidomide which is a bioisostere of thalidomide, but, in sharp contrast to the latter, it is configurationally stable and readily available in both enantiomeric forms. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The extent of oxidation of thalidomide is very low. It is known that only the ( S )-enantiomer of thalidomide is teratogenic (7, 8). We made a direct comparison of the formation of the GSH conjugate from ( R )- and ( S )-thalidomide (Figure 5) and found that the yields are similar.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of oxidation of thalidomide is very low. It is known that only the ( S )-enantiomer of thalidomide is teratogenic (7, 8). We made a direct comparison of the formation of the GSH conjugate from ( R )- and ( S )-thalidomide (Figure 5) and found that the yields are similar.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, thalidomide was similarly designated for the treatment of refractory multiple myeloma in 2005 as an "orphan" drug (Sembongi et al, 2008), and a decision regarding final approval is expected in 2008. Many clinical trials with thalidomide are ongoing for both anti-inflammatory and antiangiogenic activities (Vogelsang et al, 1992;Macpherson et al, 2003;Kamikawa et al, 2006;Breitkreutz and Anderson, 2008).…”
mentioning
confidence: 99%
“…When it was introduced half a century ago, it was used for inhibiting immune and inflammatory responses mostly in pregnant women. 20 The previous studies reported that thalidomide dramatically decreased the glial activation and the beta amyloid neuropathology in a transgenic mouse model that showed symptoms of Alzheimer's disease. 18 Unfortunately, each mirror image form of the chiral drug had different biological activities, some causing serious toxicity such as those of the (S)-thalidomide.…”
Section: Introductionmentioning
confidence: 99%